Traditional Indian Herbal Medicine: Boerhaavia diffusa (L.) - A Review - Joshi, Anita (International Journal of Pharmaceutical & Biological Archive, 2016)
Boerhavia diffusa is a trailing herb which is found throughout India. The whole plant or its specific parts (leaves, stem, and roots) are known to have medicinal properties and have a long history of use by indigenous and tribal people in India. The whole Plant or its peculiar parts have a numerous medicinal properties in treatment of stress, dyspepsia, abdominal pain, inflammation, jaundice. Chemical analysis of Boerhavia diffusa gives a wide variety of chemical constituents, namely, rotenoids, flavonoids, xanthones, purine nucleoside, lignans, and steroids. More research needs to be carried out in formulating new medicines which can contribute to animal life and mankind.